Evolution of Structural and Functional Diversity of Spexin in Mammalian and Non-mammalian Vertebrate Species - Lim, Chor Hong; Lee, Megan You Min; Soga, Tomoko; Parhar, Ishwar (Frontiers in Endocrinology, 2019)
Spexin (SPX) is a novel neuropeptide, which was first identified in the human genome using bioinformatics. Since then, orthologs of human SPX have been identified in mammalian and non-mammalian vertebrates. The mature sequence of SPX, NWTPQAMLYLKGAQ, is evolutionally conserved across vertebrate species, with some variations in teleost species where Ala at position 13 is substituted by Thr. In mammals, the gene structure of SPX comprises six exons and five introns, however, variation exists within non-mammalian species, goldfish and zebrafish having five exons while grouper has six exons. Phylogenetic and synteny analysis, reveal that SPX is grouped together with two neuropeptides, kisspeptin (KISS) and galanin (GAL) as a family of peptides with a common evolutionary ancestor. A paralog of SPX, termed SPX2 has been identified in non-mammalians but not in the mammalian genome. Ligand-receptor interaction study also shows that SPX acts as a ligand for GAL receptor 2 (2a and 2b in non-mammalian vertebrates) and 3. SPX acts as a neuromodulator with multiple central and peripheral physiological roles in the regulation of insulin release, fat metabolism, feeding behavior, and reproduction. Collectively, this review provides a comprehensive overview of the evolutionary diversity as well as molecular and physiological roles of SPX in mammalian and non-mammalian vertebrate species.